ANALISIS PERBANDINGAN TINDAK PIDANA PERZINAAN: PASAL 284 KUHP LAMA (WvS) DAN PASAL 411 KUHP NASIONAL - Aswandi, Aswandi; Harefa, Safaruddin (TANJUNGPURA LAW JOURNAL, 2026)
Abstract The regulation of the criminal offense of adultery in Indonesian criminal law has undergone significant changes following the enactment of Law No. 1 of 2023 concerning the Indonesian Criminal Code. Previously, adultery was governed under Article 284 of the old Criminal Code (KUHP), a legacy of Dutch colonial law based on the Continental European legal tradition. This provision narrowly defined adultery as a violation of marital fidelity and classified it as an absolute complaint-based offense. However, shifts in social, cultural, and religious values within Indonesian society have created a need for legal reform that better reflects the nation’s identity. This study aims to compare the regulation of adultery under Article 284 of the old Criminal Code and Article 411 of the new Criminal Code, as well as to examine its implications for the development of Indonesia’s national criminal law system. The research employs a qualitative method with a normative juridical approach through library research of relevant legislation and legal literature. The findings indicate that Article 411 of the new Criminal Code expands the concept of adultery by no longer limiting it to marital status, but defining it as a violation of social morality. Nevertheless, it maintains the complaint-based offense mechanism to balance public moral protection and individual privacy rights. The novelty of this study lies in its clear emphasis on the paradigm shift from a colonial, individualistic criminal law approach to a national criminal law system grounded in Pancasila values, analyzed through a comparative and integrated framework. The study implies that this reform strengthens the transformation of Indonesian criminal law toward a more contextual and nationally rooted legal system, while striving to balance legal certainty, justice, and prevailing social values.   Abstrak Pengaturan tindak pidana perzinaan dalam hukum pidana Indonesia mengalami perubahan signifikan dengan disahkannya Undang-Undang Nomor 1 Tahun 2023 tentang Kitab UndangUndang Hukum Pidana. Selama ini, perzinaan diatur dalam Pasal 284 KUHP lama yang merupakan warisan hukum kolonial Belanda dengan pendekatan sempit, yaitu sebagai pelanggaran terhadap kesetiaan dalam perkawinan dan bersifat delik aduan absolut. Perubahan sosial, budaya, dan nilai keagamaan masyarakat Indonesia menuntut adanya pembaruan hukum pidana yang lebih sesuai dengan karakter bangsa. Penelitian ini bertujuan untuk menganalisis perbandingan ketentuan tindak pidana perzinaan dalam Pasal 284 KUHP lama dan Pasal 411 KUHP Nasional serta mengidentifikasi implikasinya terhadap pembangunan hukum pidana nasional Indonesia. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan yuridis normatif melalui studi kepustakaan terhadap peraturan perundangundangan dan literatur hukum terkait. Hasil penelitian menunjukkan bahwa Pasal 411 KUHP Nasional memperluas konsep perzinaan dengan tidak lagi membatasi pada status perkawinan, melainkan sebagai pelanggaran terhadap kesusilaan sosial. Meskipun demikian, KUHP Nasional tetap mempertahankan mekanisme delik aduan sebagai bentuk keseimbangan antara perlindungan moral publik dan penghormatan terhadap hak privat individu. Novelty penelitian ini terletak pada penegasan pergeseran paradigma perzinaan dari hukum kolonial yang individualistik menuju hukum pidana nasional yang berlandaskan nilai Pancasila secara komparatif dan terintegrasi. Implikasi penelitian menunjukkan bahwa pembaruan ini memperkuat arah transformasi hukum pidana Indonesia menuju sistem hukum yang lebih kontekstual, berkarakter nasional, serta berupaya menyeimbangkan kepastian hukum, keadilan, dan nilai sosial masyarakat.